FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KADAR HEMOGLOBIN PADA IBU HAMIL TM III DI WILAYAH KERJA PUSKESMAS WINONG KEMIRI KABUPATEN PURWOREJO - Oktavianingtias, Setya; Lijannah, Shofiana; hasan, hasan (Jurnal Komunikasi Kesehatan, 2025)
During TM III, maternal hemoglobin levels will decrease, anemia occurs whenhemoglobin <11 gr/dL. Anemia in pregnancy reduces the amount of oxygen bound in theblood, causing the uterine muscles to not contract properly, causing postpartumhemorrhage. This study aims to determine the relationship between age, parity,nutritional status, educational status, and employment status with hemoglobin levels inpregnant women in TM III at the Winong Kemiri Health Center. Data collection wascarried out using a cross-sectional method where cause and effect variables weremeasured or collected simultaneously. This study was conducted in July 2024 at theWinong Kemiri Health Center, using the Accidental Sampling method with 20respondents. From the results of the study, a p-value <0.05 was obtained, namely agewith an hb level of 0.004, parity with an hb level of 0.029, nutritional status with an hblevel of 0.019, educational status with an hb level of 0.004, and p-value> 0.05, namelyemployment status with an hb level of 0.375. Conclusion: There is a relationship betweenhemoglobin levels with age, parity, nutritional status, and educational status, and thereis no relationship between hemoglobin levels and employment status. Suggestion:Midwives are expected to pay attention to factors related to pregnant women's Hb levelsso that they can anticipate and carry out further treatment if necessary